Playthrough Poetics (Amherst College Press, 2024)
Game streamers and live commentators are producing increasingly comprehensive analyses of gameplay, yet scholarship still tends to flatten the experiential media of video games into text for close reading. By shifting focus toward the immersiveness of video games, Playthrough Poetics makes the case for gameplay as a necessary, alternate method. Contributors to this volume engage widely with the activity of play through autoethnographies, meta-analyses of self-broadcasting, new procedural methods like gamespace soundwalking, as well as the affective aspects of games research. In doing so, they model new possibilities for academic players and gamers alike.